Application of the resonant energy separation effect at natural gas reduction points in order to improve the energy efficiency of the gas distribution system - Andrei M. Schipachev; Alena S. Dmitrieva (Записки Горного института, 2021)
Maintaining the gas temperature and the formation of gas hydrates is one of the main problems in the operation of gas pipelines. Development and implementation of new effective methods for heating the gas during gas reduction will reduce the cost of gas transportation, solve the problem of resource and energy saving in the fuel industry. Study is aimed at increasing the energy efficiency of the natural gas reduction process by using a resonant gas heater to maintain the set temperature at the outlet of the gas distribution station (GDS) and prevent possible hydrate formation and icing of the station equipment. Paper considers the implementation of fireless heating of natural gas and fuel gas savings of heaters due to the introduction of a thermoacoustic reducer, operating on the basis of the Hartmann – Sprenger resonance effect, into the scheme of the reduction unit. By analyzing the existing methods of energy separation and numerical modeling, the effectiveness of the resonant-type energy separation device is substantiated. Modification of the reduction unit by introducing energy separating devices into it will allow general or partial heating of natural gas by its own pressure energy. Developed technology will allow partial (in the future, complete) replacement of heat energy generation at a gas distribution station by burning natural gas.